TINJAUAN YURIDIS SURAT KETERANGAN (COVERNOTE) DALAM PEMBERIAN KREDIT KONSUMEN DENGAN JAMINAN SERTIFIKAT TANAH YANG DIBEBANKAN HAK TANGGUNGAN PADA PT. BPR TUNAS MITRA MANDIRI PEKANBARU - Tengku Indra Adiputra; Maryati Bachtiar; Dasrol ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Society generally still believe that Professional Notary And PPAT have in common, but both Profession Among these are differences, case singer or between lie caused Notary PPAT usually occupied by same thing. Notary officer sales manager that is authorized to review make authentic act and have more authority as hearts revoked Article 1 of Law No. 2 of 2014 ABOUT Amendment Act No. 30 of 2004 ABOUT Notary. And in deed between letter made by Notaries, Notary usually make certificate also, only prayer is a form of letter